Tradisi Pemberian Nama Bayi (Nahunan) Pada Masyarakat Suku Dayak Ngaju - Enjelika Habibah; Soko Alpandi; Salsabila Salsabila; Maria Estefania Gunadi; Ahmad Saefulloh (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
This paper uses the qualitative method of literature, namely exploring various relevant sources to discuss the topic and obtaining the required data, then it will explore the internalization of the values ​​contained in the nahunan ritual. In the nahunan ritual, ecological values ​​are found which indicate that there is an internalization of the concept that nature is family. This concept can support environmental preservation through the rituals of the Ngaju Dayak tribe. This concept can be developed to encourage public concern in preserving the environment. The concept is in the form of values ​​that regard nature as the human family. To carry out the Nahunan ceremony, various equipment for the Nahunan ceremony is prepared, both for the baby and for the midwife. All these ceremonies and paraphernalia are inseparable from the purpose of the Nahunan ceremony itself, which is to respect the life cycle from birth to death. The Dayak people really understand that life has a very deep meaning, all of which are contained in the various ceremonies held, including the Nahunan ceremony.